2014
DOI: 10.1136/bjophthalmol-2014-305774
|View full text |Cite
|
Sign up to set email alerts
|

Retinal detachment in England: database studies of trends over time and geographical variation

Abstract: Admission rates seem to have increased in recent years. This increase is probably attributable to an increase in the prevalence of diabetes, and so an increase in RD associated with diabetes. Understanding trends over time, and geographical variation, in RD will help match capacity in retinal surgery with need for treatment of RD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 23 publications
0
27
0
2
Order By: Relevance
“…Shah et al. () observed an increase in RD associated with diabetes. In our study, the overall incidence rate for RD increased during the study period, but the incidence of primary operation for TRD decreased (Table ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Shah et al. () observed an increase in RD associated with diabetes. In our study, the overall incidence rate for RD increased during the study period, but the incidence of primary operation for TRD decreased (Table ).…”
Section: Discussionmentioning
confidence: 96%
“…Broe et al (2015) found that diabetic retinopathy was an independent predictor for vitrectomy in young people with Type 1 diabetes. Shah et al (2015) observed an increase in RD associated with diabetes. In our study, the overall incidence rate for RD increased during the study period, but the incidence of primary operation for TRD decreased (Table 2).…”
Section: Incidences For Rd In the Region Of Southern Denmarkmentioning
confidence: 89%
“…Macula-on rhegmatogenous retinal detachment (RD) is a common cause of ophthalmic emergency that requires surgical treatment in a short period of time to prevent visual loss [ 1 ]. The annual incidence of RD varies according to the recent references between 15.4 [ 2 ] and 18.2 per 100 000, with a peak incidence of 52.5 per 100 000 people between 55 and 59 years of age [ 3 ]. Myopia is a major risk factor, with a 4-fold higher risk of RD, compared with a nonmyopic eye, in eyes with mild myopia and a 10-fold higher risk in eyes with moderate and high myopia (greater than −3 diopters) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite excellent surgical success rates, with an anatomical reattachment reaching up to 94% [1, 2], visual recovery varies after rhegmatogenous retinal detachment (RD). The postoperative quality of vision may be disappointing for both the patient and the surgeon [3].…”
Section: Introductionmentioning
confidence: 99%